Impact of Heavy-Duty Diesel Truck Activity on Fuel Consumption and Its Implication for the Reduction of Greenhouse Gas Emissions. Issue 3 (March 2019) - Collier, Sonya; Ruehl, Chris; Yoon, Seungju; Boriboonsomsin, Kanok; Durbin, Thomas D.; Scora, George; Johnson, Kent; Herner, Jorn
Activity data from 79 line-haul and vocational trucks were analyzed to estimate trip-averaged fuel consumption per distance driven and per work performed. The 79 trucks had engine model years ranging from 2008 to 2015 and average (±standard deviation) miles per gallon of 5.5 ± 1.7, which is comparable to other large fleet studies. Engine output work used to overcome various forms of resistance was minimized at vehicle speeds between 54 and 60 mph, which led to best fuel economy. The average gallons-per-brake horsepower-hour (gal/BHP-HR) was 0.058 ± 0.0085. When comparing the gal/BHP-HR per trip speed, higher average trip speeds led to improved fuel economy (lower gal/BHP-HR). In the case of out-of-state line-haul trucks, fuel economy was also dependent on model year. The newer model year out-of-state line-haul truck (2014) had a significant improvement in fuel economy compared with the older model year trucks (2012 and 2013). This could be the result of more stringent CO2 emission standards beginning for model year 2014 trucks under the Phase 1 Greenhouse Gas rule, but data on more vehicles would further corroborate this. The trip-averaged CO2 emissions were calculated for each truck and it was found that some truck groups displayed consistent trip-averaged emissions whereas others displayed high variability despite belonging to the same fleet. Several of the trucks engaged in significant idling, with a median contribution to their CO2 emissions of 4.2%.